2013
DOI: 10.1097/bth.0b013e318298b39d
|View full text |Cite
|
Sign up to set email alerts
|

Olecranon Osteotomy Fixation Using a Novel Device

Abstract: A posterior approach to the elbow utilizing an olecranon osteotomy has been shown to provide excellent visualization of the distal humerus articular surface. However, many bony stabilization and fixation methods for the olecranon osteotomy are usually prominent, frequently symptomatic, and often require a second operation for removal. This paper evaluates the use of an innovative device, the olecranon sled, in fixation of olecranon osteotomies for exposure of intra-articular distal humerus fractures and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This fact of the anatomy of the ulna contributes to the screw clamping screw in both fragments at the end of the surgery. The V-shaped Chevron olecranon osteotomy increases the stability of the fixation over the horizontal osteotomy, as well as increasing bone contact surface between the fragments, favouring their consolidation [10,17,19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact of the anatomy of the ulna contributes to the screw clamping screw in both fragments at the end of the surgery. The V-shaped Chevron olecranon osteotomy increases the stability of the fixation over the horizontal osteotomy, as well as increasing bone contact surface between the fragments, favouring their consolidation [10,17,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 Wagener [19] used intramedullary cancellous screw and suture tension band with very good results in 19 patients. Iorio uses a novel device (the olecranon sled), obtains excellent rates of union [10].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, there are limited reports on the use of the Olecranon Sled in the literature. 9,13 Iorio et al 9 reported their use of olecranon osteotomies repaired with the Olecranon Sled. Of 14 patients, 1 (7.1%) had symptomatic hardware requiring removal; this is far below tension band construct rates.…”
Section: Discussionmentioning
confidence: 99%
“…5 Limited clinical data are available on the use of the Olecranon Sled. 9,13 Iorio et al 9 reported on 14 patients, with 1 requiring hardware removal. In a larger case series, Lovy et al 13 found no instances of nonunion, malunion, or hardware removal.…”
mentioning
confidence: 99%
“…In this case, the metacarpal sled simulates a tension band construct where the outer portion of the plate is located on the tension side of the fracture so that normal flexion forces across the metacarpal compresses the fracture. Similar sled constructs have been commercially available for fixation of medial malleolus ankle fracture and olecranon fracture [6,15].…”
Section: Discussionmentioning
confidence: 99%